2021
DOI: 10.3389/fgene.2020.615680
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Prognostic Signature Based on Single-Cell RNA Sequencing Data of Immune Cells in Intrahepatic Cholangiocarcinoma

Abstract: Analysis of single-cell RNA sequencing (scRNA-seq) data of immune cells from the tumor microenvironment (TME) may identify tumor progression biomarkers. This study was designed to investigate the prognostic value of differentially expressed genes (DEGs) in intrahepatic cholangiocarcinoma (ICC) using scRNA-seq. We downloaded the scRNA-seq data of 33,991 cell samples, including 17,090 ICC cell samples and 16,901 ICC adjacent tissue cell samples regarded as normal cells. scRNA-seq data were processed and classifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 37 publications
(23 reference statements)
0
13
0
Order By: Relevance
“…Using a molecular approach, eCCAs were classified in metabolic, mesenchymal, proliferative, and immune classes, all characterized in terms of mutations and modulation of different actionable targets. Furthermore, the development of single-cell RNA sequencing now allows analysis of the discrete cell populations in the TRS, including CAFs [119] and immune response cells [120] , and to study in more detail the crosstalk between these cell milieus [121] . Finally, a recent study used nano liquid chromatography coupled to matrix-assisted laser desorption/ionization-time of flight (MALDI-TOF/TOF) analysis to study the composition of the matrix (or matrisome) in CCA [122] .…”
Section: Discussionmentioning
confidence: 99%
“…Using a molecular approach, eCCAs were classified in metabolic, mesenchymal, proliferative, and immune classes, all characterized in terms of mutations and modulation of different actionable targets. Furthermore, the development of single-cell RNA sequencing now allows analysis of the discrete cell populations in the TRS, including CAFs [119] and immune response cells [120] , and to study in more detail the crosstalk between these cell milieus [121] . Finally, a recent study used nano liquid chromatography coupled to matrix-assisted laser desorption/ionization-time of flight (MALDI-TOF/TOF) analysis to study the composition of the matrix (or matrisome) in CCA [122] .…”
Section: Discussionmentioning
confidence: 99%
“…PDGFD signaling in GBM was shown to induce IFN-g secretion by natural killer cells through the engagement of the human immunoreceptor NKp44 (33). Meanwhile, PDGFD was an important predictor gene for bladder cancer, renal clear cell carcinoma, and osteosarcoma (34)(35)(36). It has been found that TUBB3 was highly expressed in lung neuroendocrine carcinoma and medulloblastoma, which was associated with positive lymphatic permeation (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…Dimension reduction analysis was performed with the Seurat “RunPCA” function, and non-linear dimensional reduction was performed with the Seurat “RunUMAP” function. The tSNE analysis was used for dimension reduction to determine the cell populations and for visualization of the gene expression ( 14 ). The FindClusters function was performed with a resolution of 0.5, and the RunTSNE function was used to generate clusters.…”
Section: Methodsmentioning
confidence: 99%
“…Miao Su et al. established nine-prognosis-related-genes (PRGs) by reanalyzing the ScRNA-seq ( 14 ). These genes included SLC16A3, BNIP3L, TPM2, CLEC11A, EREG, PMAIP1, CEBPB, A2M, and TUBA1B, which are correlated with ICC prognosis ( 14 ).…”
Section: Introductionmentioning
confidence: 99%